Reliability Indicators of 10 kV Cable Lines in Rural Areas - A.D.Taslimov (International Journal of Advanced Science and Technology, 2020)
Based on statistical data, the article analyzes and proposes a combination method for calculating the reliability indicators of power supply to agricultural consumers (equivalent duration of outages, frequency of failures and deliberate outages, recovery time) when using cable and overhead lines. It has been established that the reliability of rural cable lines is slightly higher than overhead and the use of cables in rural electric networks improves the reliability of power supply to consumers by eliminating failures, and also leads to an increase in the reliability of transformer substations by reducing the number of damage to transformers.